2005
DOI: 10.1124/jpet.104.082099
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gene Markers of Fibrosis with a Novel Inhibitor of Transforming Growth Factor-β Type I Receptor Kinase in Puromycin-Induced Nephritis

Abstract: SB-525334 (6-[2-tert-butyl-5-(6-methyl-pyridin-2-yl)-1H-imidazol-4-yl]-quinoxaline) has been characterized as a potent and selective inhibitor of the transforming growth factor-␤1 (TGF-␤1) receptor, activin receptor-like kinase (ALK5). The compound inhibited ALK5 kinase activity with an IC 50 of 14.3 nM and was ϳ4-fold less potent as an inhibitor of ALK4 (IC 50 ϭ 58.5 nM). SB-525334 was inactive as an inhibitor of ALK2, ALK3, and ALK6 (IC 50 Ͼ 10,000 nM). In cell-based assays, SB-525334 (1 M) blocked TGF-␤1-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
131
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 25 publications
4
131
0
Order By: Relevance
“…This lack of cross-reactivity serves to demonstrate that the physeal effects were a function of ALK inhibition at toxicologic, suprapharmacologic doses rather than off-target pharmacology. Closely related ALK5 inhibitors were previously assayed for effects on other ALK family members (Inman, 2002;Grygielko, 2005). These inhibitors were approximately 10-20-fold less potent as inhibitors of ALK4 and ALK7, and 100-fold less potent as inhibitors of ALK3 and ALK6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of cross-reactivity serves to demonstrate that the physeal effects were a function of ALK inhibition at toxicologic, suprapharmacologic doses rather than off-target pharmacology. Closely related ALK5 inhibitors were previously assayed for effects on other ALK family members (Inman, 2002;Grygielko, 2005). These inhibitors were approximately 10-20-fold less potent as inhibitors of ALK4 and ALK7, and 100-fold less potent as inhibitors of ALK3 and ALK6.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds were also evaluated in the purine aminonucleoside nephrosis (PAN) rodent model (Grygielko et al, 2005). Briefly, Sprague-Dawley rats were pretreated by oral gavage with 1,3, or 10 mg/kg/day GW788388 once daily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using pharmacological inhibitors, Grygielko et al (38) showed that SB525334, a selective ALK5 inhibitor, reduced proteinuria in adriamycin-induced nephrosis in rats. ALK inhibitors act by suppression of TGF-β/Smad signals and inhibition of autoinduction of TGF-β and possibly activin βA (39).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to inhibit the catalytic activity of ALK5 by using ATP-competitive small molecule inhibitors have been one of the most successful strategies to interfere with the in vivo signaling of TGF-β. These small molecule inhibitors have been proven to prevent kidney and lung fibrosis in animal models [25][26][27] and have shown to possess potent anti-tumor and antimetastatic activity in animal experiments [28][29][30][31][32][33] A-83-01 is also one of the potent small molecule ATP-competitive inhibitors against ALK5 and has been shown to inhibit TGF-β1-dependent cancer metastasis by inhibiting EMT in animals. 19,34) In this report, we attempted to inhibit the TGF-β signaling during burn wound healing in rat skin by using topical application of A-83-01 and evaluated its effect on wound contraction and closing.…”
Section: Discussionmentioning
confidence: 99%